Adapting and Validating the Sexual Experiences Questionnaire to Study Sexual Harassment Among University Women in Jordan. Issue 19 (October 2022) - Spencer, Rachael A.; Yount, Kathryn M.; Essaid, Aida A.; Cheong, Yuk Fai; Sajdi, Jude; Taleb, Rand Abu; Bergenfeld, Irina; Batayeh, Brian; Sandhu, Seema; Robbin, Zoe; Zwooqar, Ahad; Clark, Cari Jo
Despite the adverse effects of sexual harassment, measurement gaps persist. Using a sequential, mixed-methods approach, we adapted and validated the Sexual Experiences Questionnaire (SEQ) to measure sexual harassment victimization among college-going women in Jordan. From a 213-item pool and qualitative data from students at the study site, we removed 50 items and collapsed or rephrased 163 items into selected 27 items for examination. After expert reviewers and study-site staff assessed content validity, we replaced three items. Items were tested using cognitive interviews ( n = 7) and then administered in a survey to 567 women students. We sequentially performed exploratory factor analysis (EFA) with a random split-half sample ( N 1 = 283), confirmatory factor analysis (CFA) with the second sample ( N 2 = 284), and confirmatory bifactor analysis. Five items with cross-factor loadings were dropped. Model fit for the final four-factor EFA and CFA was adequate (EFA: RMSEA: 0.013, CFI: 0.996, TLI: 0.994; CFA: RMSEA 0.020, CFI: 0.988, TLI: 0.986). Three factors were similar to those identified in the SEQ—gender harassment, sexual coercion, and unwanted sexual attention—but we also identified a fourth factor—physical-contact sexual harassment. The bifactor analysis suggested that the scale was unidimensional (general factor ECV=.701 and PUC =.727). The unidimensional scale was positively associated with depressive symptoms. Using an adapted SEQ, sexual harassment is a measurable construct in the Jordanian university context. Further validation of this tool and efforts to capture each dimension of sexual harassment in the Arab region is needed.